Target Genes of Autism Risk Loci in Brain Frontal Cortex - Sun, Yan; Yao, Xueming; March, Michael E.; Meng, Xinyi; Li, Junyi; Wei, Zhi; Sleiman, Patrick M.A.; Hakonarson, Hakon; Xia, Qianghua; Li, Jin (Frontiers in Genetics, 2019)
Autism spectrum disorder (ASD) is a complex neuropsychiatric disorder. A number of genetic risk loci have been identified for ASD from genome-wide association studies (GWAS), however, their target genes in relevant tissues and cell types remain to be investigated. Frontal cortex is a key region in human brain for communications and cognitive functions. To identify risk genes contributing to the dysfunction of ASD brain frontal cortex, we took an in silico approach integrating multi-omics data. We first found genes the expression of which is correlated with ASD risk loci by leveraging expression quantitative trait loci (eQTLs) information. Among these genes, we then identified 76 genes showing significant differential expression between ASD cases and controls in microarray datasets and further replicated 4 genes by RNA-seq data. Among the ASD GWAS SNPs correlating with the 76 genes, 20 overlap with histone marks and 45 are associated with gene methylation level. Thus, through multi-omics data analyses, we identified genes that may work as target genes of ASD risk loci in the brain frontal cortex.